Reservoir characteristics and 3D static modelling of the Late Miocene Abu Madi Formation, onshore Nile Delta, Egypt. (August 2017) - El Khadragy, A.A.; Eysa, E.A.; Hashim, A.; Abd El Kader, A.
Abstract: West Al Khilala Field is considered as gas producing from Abu Madi Miocene sandstone Formation. It lies at the central onshore Nile Delta and covers about 47.6 km 2 . The petrophysical parameters (porosity, permeability, water saturation and net-to-gross ratio) as well as static modelling of the Abu Madi reservoir from well logs are carried out. The porosity model reflected good porosity in the study area especially in the massive sandstone unit with values range from 18% to 27%, while low porosity value are recorded in the layered and basal sandstone units with values range from 1% to 24%. The permeability model displayed values range from 50 md to 2000 md in the massive sandstone unit that increases towards the southeast direction reflected a high promising for hydrocarbon prospecting. The permeability values of the layered and basal sandstone units range from 0.5 md to 700 md with mean value of 40 md reflected a tight permeability due to the presence of shale streaks. The water saturation (Sw) model of the layered and massive sandstone units indicated hydrocarbon-bearing intervals with values from 10% to 64.7%, while the basal sandstone unit is highly saturated with water from 65% up to 100%. The volumetric calculation of the reservoir showed that the reservoir contained about 246 BSCF as a recoverable gas. Highlights: West Al Khilala Field. Nile Delta. Reservoir Characterization. Reservoir Modelling.